Detection of soy in food from the Czech market using ELISA and PCR methods - Kamila Novotná Kružíková; Tereza Popelková; Zuzana Tšponová; Veronika Doubková; Petra Doleželová; Lucie Laichmannová (Czech Journal of Food Sciences, 2022)
Soy is considered an allergen under Regulation No. 1169/2011 of the European Parliament and of the Council, which mandates the labelling of soy allergen on food packaging. This study is focused on detecting soy in food products using two kinds of methods. The first method, enzyme-linked immunosorbent assay (ELISA), was performed using two commercial kits (Veratox for Soy Allergen; Neogen, USA). The second method, polymerase chain reaction (PCR), was carried out with two different deoxyribonucleic acid (DNA)-isolating kits and DNA isolation via the cetyltrimethylammonium bromide (CTAB) method. A total of 57 samples of food were tested, including 45 samples of animal origin and 12 samples of plant origin. The results were compared with information on the packaging. From the group of samples that contained soy according to the packaging (12 pieces), 9 samples were found to be positive by ELISA method, 10 samples by the CTAB method and 11 samples by GeneSpin. On the other hand, from the group of samples that should not contain soy according to the packaging (30 pieces), the presence of soy in 2 samples was detected by ELISA. No significant difference was found between the examined methods. Results show that the situation on the market is satisfactory and that only products declared as containing traces of soy appear to be problematic.